2010
DOI: 10.1530/rep-10-0211
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 2 inhibits FSH responsiveness in hen granulosa cells

Abstract: Prior to follicle selection into the preovulatory hierarchy, hen granulosa cells from prehierarchal follicles remain undifferentiated, as defined in part by the virtual absence of LHR mRNA expression and inability to produce progesterone. It has previously been proposed that prior to follicle selection, granulosa cells are actively maintained in an undifferentiated state by epidermal growth factor receptor ligands (EGFRL) signaling via the MAP kinase/extracellular regulated kinase pathway. Moreover, there is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Western blot analysis for STAR, phospho-SMAD, and total SMAD proteins was conducted essentially as described previously (Haugen & Johnson 2010). Briefly, cells were homogenized in a protein lysis buffer (RIPA, Santa Cruz Biotechnology, Santa Cruz, CA, USA) containing a cocktail of enzyme (including phosphatase) inhibitors (Sigma-Aldrich).…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Western blot analysis for STAR, phospho-SMAD, and total SMAD proteins was conducted essentially as described previously (Haugen & Johnson 2010). Briefly, cells were homogenized in a protein lysis buffer (RIPA, Santa Cruz Biotechnology, Santa Cruz, CA, USA) containing a cocktail of enzyme (including phosphatase) inhibitors (Sigma-Aldrich).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…A previous report has identified mRNA expression for both BMP type I (BMPR1A and BMPR1B) and type II (BMPR2) membrane receptors in hen granulosa cells (Onagbesan et al 2003). In turn, BMP-activated receptor complexes signal via SMAD1/ 5/8 (Haugen & Johnson 2010). By comparison, mammalian AMH signals via a BMP type I receptor (including ACVR1B (ACTR1A)/ACVR1 (ALK2) and BMPR1B/ALK6) that complexes with an AMH-specific type II receptor (Visser 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adult chicken ovary, BMP signaling is involved in maintenance of follicles in an undifferentiated state prior to follicle selection [Haugen and Johnson, 2010], yet BMP signaling may also play a role in the developing chicken ovary. Recent expression analysis in chicken embryos has shown that various TGF-␤ family signaling molecules and effector proteins are upregulated in ZW gonads during and after sexual differentiation, including several BMPs (BMP2, 3, 4 and 7) [Carré et al, 2011].…”
Section: Additional Signaling Pathways That May Regulate Ovarian Devementioning
confidence: 99%
“…Circulating levels of FSH and its receptor (FSHR) expressions on granulosa cells play a decisive role in avian follicular selection. In the avian ovary, prior to follicle selection, the granulosa cells from prehierarchical follicles remain undifferentiated, as defined by high FSHR mRNA expression, as well as the low expression of luteinizing hormone receptor (LHR) mRNA (Haugen and Johnson, 2010).…”
Section: Introductionmentioning
confidence: 99%